KONFLIK DAN INTEGRASI (STUDI TERHADAP PENGEMBANGAN BUDAYA DAN KEARIFAN LOKAL DI KECAMATAN LEMPUING DAN LEMPUING JAYA) - Hamidah Hamidah; Siti Afiqah Bt Mohamed Tahir (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2018)
The Study of Conflict and Integration (Study on Cultural Development and Local Wisdom in Lempuing and Lempuing Jaya Subdistricts) is a qualitative research with analytical descriptive research type using Sociological Approach, Historical Approach and Ethnological Approach. Some concepts that can be recorded are